In vivo Assessment of Myocardial Stiffness with Acoustic Radiation Force Impulse Imaging - Hsu, Stephen J. (2007)
Acoustic radiation force impulse (ARFI) imaging has been demonstrated to be capable of visualizing variations in local stiffness within soft tissue. Recent advances in ARFI beam sequencing and parallel imaging have shortened acquisition times and lessened transducer heating to a point where ARFI acquisitions can be executed at high frame rates on commercially available diagnostic scanners. In vivo ARFI images were acquired with a linear array placed on an exposed canine heart. The electrocardiogram (ECG) was also recorded. When co-registered with the ECG, ARFI displacement images of the heart reflect the expected myocardial stiffness changes during the cardiac cycle. A radiofrequency ablation was performed on the epicardial surface of the left ventricular free wall, creating a small lesion that did not vary in stiffness during a heartbeat, though continued to move with the rest of the heart. ARFI images showed a hemispherical, stiffer region at the ablation site whose displacement magnitude and temporal variation through the cardiac cycle were less than the surrounding untreated myocardium. Sequences with radiation force pulse amplitudes set to zero were acquired to measure potential cardiac motion artifacts within the ARFI images. The results show promise for real-time cardiac ARFI imaging.